Sensitivity of spectral domain optical coherence tomography in the diagnosis of posterior vitreous detachment in vitreomacular interface disorders: A prospective cohort study. Issue 2 (March 2022) - Stavrakas, Panagiotis; Christou, Evita Evangelia; Ananikas, Konstantinos; Tsiogka, Anastasia; Tranos, Paris; Theodossiadis, Panagiotis; Stefaniotou, Maria; Chatziralli, Irini
Purpose: To evaluate the sensitivity of Spectral Domain Optical Coherence Tomography (SD-OCT) regarding the diagnosis of posterior vitreous detachment (PVD) in vitreomacular interface disorders (VID). Methods: A total of 48 eyes of 48 patients were included in this prospective cohort study. PVD in eyes with VID was investigated. We determined the status of posterior vitreous cortex using slit lamp (SL) biomicroscopy and SD-OCT preoperatively, during vitrectomy and on the intraoperative video recording. Sensitivity and specificity of the examining methods were analysed. Four masked independent examiners participated in this study. Results: PVD was diagnosed in 16 eyes (33.3%) on SD-OCT, 20 eyes (41.7%) on SL examination and 28 eyes (58.3%) during vitrectomy. Sensitivity and specificity for diagnosis of PVD was 37.5% and 31.3% using SD-OCT, 90% and 64.3% on the SL examination, 92.9% and 90% on the video recording respectively, compared to the intraoperative PVD diagnosis. Conclusion: SD-OCT shows a relatively low detection sensitivity of PVD in VID. Thorough OCT investigation is necessary to establish an appropriate diagnosis of PVD and treatment in VID.